Evolution of pain at 3 months by oral resveratrol in knee osteoarthritis (ARTHROL): protocol for a multicentre randomised double-blind placebo-controlled trial. Issue 9 (29th September 2017) - Nguyen, Christelle; Boutron, Isabelle; Baron, Gabriel; Coudeyre, Emmanuel; Berenbaum, Francis; Poiraudeau, Serge; Rannou, François
Abstract : Introduction: Osteoarthritis (OA) pathophysiology is driven in part by joint inflammation. Resveratrol has in vitro anti-inflammatory properties. We aim to assess the efficacy of oral resveratrol for knee pain at 3 months in people with knee OA. Methods and analysis: We will conduct a randomised double-blind placebo-controlled trial. Overall, 164 individuals with knee OA fulfilling 1986 American College of Rheumatology criteria will be recruited in three tertiary care centres in France and randomised to receive oral resveratrol, 40 mg (two caplets) two times per day for 1 week, then 20 mg (one caplet) two times per day or a matching placebo for a total of 6 months. Randomisation will be centralised and stratified by centre. The allocation ratio of assignments will be 1:1. The primary outcome will be the mean change from baseline in knee pain on a self-administered 11-point pain Numeric Rating Scale at 3 months. Secondary outcomes will be the mean change in knee pain at 6 months, the function subscore of the Western Ontario and McMaster Universities Arthritis Index score, patient global assessment, proportion of responders according to the Osteoarthritis Research Society International–Outcome Measures in Rheumatology criteria at 3 and 6 months, and self-reported number of intra-articular injections of corticosteroids or hyaluronic acid and consumption of analgesics and non-steroidal anti-inflammatory drugs since the last contact. Other interventions will be allowed and self-reported. Adherence will be monitored by capsule counts and a booklet and adverse events recorded at 3 and 6 months. Statisticians, treating physicians and participants will be blinded to the allocated treatment. Ethics and dissemination: The oral resveratrol in knee osteoarthritis (ARTHROL) trial has been authorised by the AgenceNationale de Sécurité du Médicament et des Produits de Santé and ethics were approved by the Comité deProtection des Personnes Île-de-France III. The findings of the study will be published in a peer-reviewed journal and disseminated at conferences. The design of ARTHROL will warrant the translation of its findings into clinical practice. Trial registration number: ClinicalTrials.gov identifier: NCT02905799 . Pre-results. First received: 14 September 2016. Last updated: 16 September 2016. Status: not yet recruiting.